Business Registration Reform Case Studies : Estonia - Olaisen, John (World Bank, Washington, DC, 2017)
This case study describes the experiences and draws lessons from varied business registration reform programs in economies in vastly different stages of development: Bulgaria, Estonia, Ireland, Madagascar, and Malaysia. The case studies were written based on a desk study of reforms in each country discussed. Then, more detailed information was gathered by field?based researchers. In some cases, detail on the business registration process that was in place prior to implementation of reforms was unavailable. As such, data on the number of businesses registered and the time required to completed registration before and after the reforms cannot be compared and contrasted. This case study focuses on the attempts of the government of Estonia (GoE) to promote and implement reform of the business registration system to better suit the new economic framework that emerged in the country following Estonia's independence and the collapse of the Soviet Union in 1991. The purpose of this case study is to show that 1) business registration reform can be successful, regardless of the institution in charge of the reform process; and, 2) membership (or the prospect of membership) in international trade blocs or organizations such as the European Union (EU) can be a powerful trigger for business registration reforms.